Android-Based Personal Hygiene Educational Game Application for Children - Ida, Nuraida Latif; Ratnawati; Rohayati Arifin; Wisda; Nurmila (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2023)
Presently, there remains a deficiency in educational games aimed at instilling in children an awareness of personal hygiene, and numerous health issues stem from a lack of adherence to good hygiene practices. This study seeks to develop an Android-based educational game catering to the hygiene needs of young children, with a focus on assessing the application's feasibility. The research collected system-building data through observations and interviews, employing the Black Box testing method to evaluate the application's usability. Field and library research contributed to the acquisition of comprehensive data. The study's outcome is the creation of an Android-based educational game dedicated to teaching personal hygiene to children. Utilizing the UML design method, the author constructed and integrated the game into the Unity 3D application, enabling children to grasp the significance of cleanliness and environmental hygiene through engaging gameplay. Evaluation results indicate the suitability of the personal hygiene education game, with a learning menu percentage of 78% and a play menu percentage of 77%, as determined by questionnaire-based tests, affirming the system's appropriateness for use.